Evaluation of Haematological Responses and Blood Biochemical Parameters of Heat-stressed Broilers with Dietary Supplementation of Javanese Ginger Powder (Curcuma xanthorrhiza) and Garlic Extract (Allium sativum) - Mushawwir , Andi; Tanuwiria, U Hidayat; Kamil, Kurnia A; Adriani, Lovita; Wiradimadja, Rachmat; Suwarno, Nono (International Journal of Poultry Science, 2018)
Background and Objective: Temperature is one of the main factors affecting the performance of broilers. Feed efficiency and poor performance of broilers are a main problem for broiler producers in regions in which the temperature exceeds the thermoneutral zone or even the upper critical temperature. The current experiment was conducted to evaluate the potential of combining Javanese ginger powder (JGP) with garlic extract (GE) in improving haematological condition and blood biochemistry in heat-stressed broilers. Materials and Methods: One hundred and seventy-five, one-day-old unsex Cobb broiler chicks were used in the current study to evaluate the potential of combining Javanese ginger powder (JGP) with garlic extract (GE) in improving haematological condition and blood biochemistry in heat-stressed broiler. The dietary treatments consisted of Javanese ginger powder (JGP) and garlic extract (GE). The broiler samples were randomly allocated to 7 treatment groups: Control group = D0 (without JGP and GE), JGP of 10 g kg–1 basal diet (D1), JGP of 15 g kg–1 basal diet (D2), GE of 5 mL kg–1 basal diet (D3), GE of 10 mL kg–1 basal diet (D4), JGP of 10 g: GE of 5 mL (D5) and JGP of 10 g: GE of 10 mL (D6). Blood samples were collected and whole blood was used to analyse haematological parameters while the blood plasma was used to determine the concentration of biochemical parameters by an automatic biochemical analyser, using a commercial kit. Results: The current study showed decreased haematological condition and biochemical profile in heat-stressed broilers. Combining JGP and GE can improve the physiological condition (haematological and biochemical) in heat-stressed broilers. A combination of JGP with GE (D5 and D6) demonstrated supplemented levels that significantly enhanced (p